Safe and Effective Perioperative Management in Patients with Atrial Septal Defect and Pulmonary Contusion: A Case Study with Supraclavicular Block - RTH Supraptomo; Andy Nugroho; Muhammad Baihaqi Siddik (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Peripheral nerve blocks offer a safer anesthetic alternative in patients with congenital heart disease (CHD) by reducing cardiovascular and pulmonary risks associated with general anesthesia. The supraclavicular brachial plexus block provides effective anesthesia for upper limb surgery with improved hemodynamic stability, reduced complications, and better postoperative analgesia. This case report aims to demonstrate the safety and effectiveness of supraclavicular brachial plexus block as a perioperative anesthetic strategy in a high-risk patient with CHD and pulmonary contusion.Case: A 67-year-old woman with a large secundum atrial septal defect (ASD), severe pulmonary hypertension, right ventricular dysfunction, and bilateral lung contusions on day 10 was scheduled for open reduction internal fixation (ORIF) of a distal radius fracture. Due to high cardiopulmonary risk, regional anesthesia was chosen. An ultrasound- and nerve stimulator-guided supraclavicular block using 20 mL of levobupivacaine 0.375% was performed. The procedure was completed successfully with stable hemodynamics and preserved spontaneous ventilation. Postoperatively, the patient was monitored in a high-care unit (HCU).Discussion: Maintaining hemodynamic stability and avoiding increases in pulmonary vascular resistance (PVR) are critical in acyanotic left-to-right shunt CHD. General anesthesia and mechanical ventilation may disrupt Qp:Qs balance and worsen pulmonary function, especially in pulmonary contusion. Regional anesthesia minimizes these risks while providing adequate surgical conditions.Conclusion: Supraclavicular brachial plexus block is a safe and effective alternative for upper limb surgery in high-risk CHD patients with acyanotic shunt lesions and pulmonary complications.